The Needs For Contextual In Teaching Materials On Writing Kid Stories Grade 4th Elementary School - Yermia Tri Utami; St. Y. Slamet; Winarno Winarno (Journal of Education and Learning (EduLearn), 2018)
The aims of research consist of the following (1) to know need analyze teaching materials related to the matter on writing kid stories in the fourth grade of elementary school, (2) to develop teaching material on writing kid stories based on contextual. The study employs descriptive qualitative and evaluative method which the data are collected by interview, observation, document analysis, and Forum Group Discussions (FGD), questionnaire, and test. Result of the research (1) The teachers still need the addition of teaching materials on writing kid stories as support, (2) Teachers need the new innovation about the developing og teaching materials on writing kid stories. Teaching materials on writing kid stories on contextual basis which can help the teachers as the teaching media in enlanging the sight on writing kid stories and the students are motivated in expressing idea, opinion and mind in a story. The results of the development of teaching materials to writing kid stories based on contextual grade 4th can be received well by learners.